The Synthesis and Physical Properties of Infinite Mercury Chain Conducting Materials - Chartier, Robert Duane (My University, 1982)
Novel synthetic pathways for the production of infinite mercury chain materials (Hg₃₋δMF₆) were investigated and some of the physical properties of the materials were studied. The solution chemistry of the homopolyatomic cation system (Hg₂²⁺, Hg₃²⁺, Hg₄²⁺) from which either Hg₃₋δAsF₆ or Hg₃₋δSbF₆ are formed was probed using ¹⁹⁹Hg NMR (Nuclear Magnetic Resonance).
Both O₂⁺ and NO+ salts of the ASF¯₆ or SbF¯₆ ions oxidized metallic mercury to produce the known materials Hg₃₋δMF₆.
Differential Thermal Analysis (DTA) was used to study both low and high temperature phase transitions in the conducting materials. A phase transition at approximately 235 K has been associated with the reversible anisotropic extrusion of mercury from the crystals.
The thermal and hydrolytic decomposition pathways for Hg₃₋δAsF₆ were characterized and the absolute reflectance was also measured.
Keywords: Chemistry; Chemistry